Efficiency of freight forwarder’s participation in the process of transportation - Burkovskis, Raimondas (Transport, 2008)
Freight forwarder s participation in the process of transporting goods allows his clients to refuse unnecessary services and get focussed on the main competencies of a company. At presence, there is no common definition of the term ‘freight forwarder’ or identical legal regulation of responsibility and functions; therefore, the problems of unifying the international process of goods movement are confronted. This reduces the efficiency of activity and causes additional problems in the field of international trade. In the future, freight forwarder’s role in logistics supply chain will rise and the clients will demand the whole package of logistics services. Therefore, special notice should be given to stimulate investments into the new freight forwarder’s services. First published online: 27 Oct 2010